2012
DOI: 10.1084/jem.20112012
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin expression from synovial fibroblasts is essential for the pathogenesis of modeled arthritis

Abstract: Synovial fibroblasts from patients and mice with arthritis express autotaxin, and ablation of autotaxin in fibroblasts ameliorates disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(155 citation statements)
references
References 32 publications
4
148
0
3
Order By: Relevance
“…Expression of ATX was analyzed by immunohistochemistry and ELISA. ATX was highly expressed in RA synovium compared with OA synovium ( Figure 1A), as well as in RA SF (mean Ϯ SEM 0.60 Ϯ 0.093 mg/liter; n ϭ 15) compared with OA SF (0.27 Ϯ 0.045 mg/liter; n ϭ 10) (P Ͻ 0.05), similar to previously reported findings (18). In RA ST, ATX was expressed on stromal cells, including CD68ϩ macrophages and vWF-positive endothelial cells ( Figure 1B).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Expression of ATX was analyzed by immunohistochemistry and ELISA. ATX was highly expressed in RA synovium compared with OA synovium ( Figure 1A), as well as in RA SF (mean Ϯ SEM 0.60 Ϯ 0.093 mg/liter; n ϭ 15) compared with OA SF (0.27 Ϯ 0.045 mg/liter; n ϭ 10) (P Ͻ 0.05), similar to previously reported findings (18). In RA ST, ATX was expressed on stromal cells, including CD68ϩ macrophages and vWF-positive endothelial cells ( Figure 1B).…”
Section: Resultssupporting
confidence: 90%
“…Recent studies demonstrated that ATX was expressed on FLS and in the ST and SF of patients with RA, and that conditional genetic ablation of ATX in mesenchymal cells resulted in disease attenuation in animal models of arthritis (18). It has been suggested that the ATX/LPA axis plays an important role in the development of arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pannus formation is associated with inhibition of neutrophil infiltration. 25,26 Treatment with RC showed protective effect support its anti-arthritic effect. The inhibition of pannus formation and bone erosion may be associated with inhibition of neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 92%
“…embryogenesis and basic cell functions including growth, migration, DNA repair etc. Several studies indicate a role for the ATX-LPA axis in inflammatory conditions of the lung such as asthma [2] and idiopathic lung fibrosis [3] , but also in wound healing [4] , rheumatoid arthritis [5,6] and in linking inflammation and carcinogenesis in e.g. mammary cancer [7] .…”
Section: Autotaxin (Atx) the Atx-lpa Axis Inflammation And Xenobioticsmentioning
confidence: 99%